The Importance of Emotional Intelligence for Transformational Leaders: A Critical Analysis - Munir, Saqib; Shakeel, Muhammad; Waheed, Khawaja Zeeshan (Pakistan Journal of Humanities and Social Sciences, 2023)
The relationship between emotional intelligence (EI) and transformational leadership (TFL) has received growing attention in recent years. The aim of the critical analysis was to explore the nature of this relationship and provide an insight into how emotional intelligence influences the transformational leadership style. The study revealed a positive and significant relationship between emotional intelligence and transformational leadership. EI has been found to be a predictor of transformational leadership, and individuals with higher emotional intelligence have been observed to exhibit transformational leadership qualities more frequently. The study highlights the need for organizations to prioritize the development of emotional intelligence in their leaders, as it can enhance their transformational leadership abilities. The critical analysis comes to the conclusion that EI is essential for transformational leaders in order to develop connections, encourage workers to reach their potential, and establish trust. Overall, this comprehensive review offers a thorough assessment of the research on TL and EI, emphasising the need of EI for effective leadership.